2020
DOI: 10.1161/strokeaha.119.027958
|View full text |Cite
|
Sign up to set email alerts
|

Vertebrobasilar Artery Calcification and Outcomes in Posterior Circulation Large Vessel Occlusion Thrombectomy

Abstract: Background and Purpose— Intracranial carotid artery calcification is associated with worse outcome in anterior circulation stroke patients who undergo endovascular thrombectomy. We investigated the association between vertebrobasilar artery calcification (VBAC) and outcome in patients undergoing endovascular thrombectomy for posterior circulation large vessel occlusion. Methods— Consecutive patients treated for posterior circulation large vessel occlusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The probability of VBAC occurring in our study was 36%, which has been identified in 21.0% of elderly community-dwelling people ( 16 ), 39.1% of people presenting posterior circulation large vessel occlusion ( 18 ), and 54.6% in ischemic stroke patients ( 19 ). Factors affecting VBAC are age, hypertension, and diabetes, findings that are consistent with the study by Janine et al ( 16 ).…”
Section: Discussionmentioning
confidence: 57%
“…The probability of VBAC occurring in our study was 36%, which has been identified in 21.0% of elderly community-dwelling people ( 16 ), 39.1% of people presenting posterior circulation large vessel occlusion ( 18 ), and 54.6% in ischemic stroke patients ( 19 ). Factors affecting VBAC are age, hypertension, and diabetes, findings that are consistent with the study by Janine et al ( 16 ).…”
Section: Discussionmentioning
confidence: 57%
“…Two studies reported that calcification volumes of the intracranial carotid artery and vertebrobasilar artery were significantly associated with worse outcomes after intra-arterial revascularization therapies. 27 , 28 Yu et al 29 reported that calcification volume on the lesion side was associated with hemorrhagic transformation after intravenous thrombolysis. Therefore, the higher volume of vertebrobasilar artery calcification observed in DM patients may substantially influence the prognostication and treatment decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…In our case series, the technical success rate was 90%, and the mortality was 0% at discharge. Complications occurred in 2 patients: asymptomatic intracranial vertebral artery dissection in one patient and subarachnoid hemorrhage in the other patient (case 6), which might be associated with heavy calcification in the intracranial vertebral artery because a recent study showed that larger vertebrobasilar artery calcification volumes were a significant predictor of reduced technical success and functional independence and increased mortality ( 22 ). Although our results seemed encouraging, it should be emphasized that revascularization of intracranial vertebral artery occlusion in the early non-acute stage is a high-risk procedure.…”
Section: Discussionmentioning
confidence: 99%